Regulating informal trading in local government : the case of Polokwane Local Municipality - Mabitsela, Phuti William (My University, 2017)
The study focuses on the regulation of informal trading, specifically street traders, within Polokwane Local Municipality. Municipalities required to manage street trading, and to deal with the challenge of increasing numbers of informal traders, which is affecting the formal trading economy. A small income and the limited ability of the government and the formal business sector to provide sufficient employment opportunities to people in the economically active age categories are two of the main reasons for informal trading in South African cities. As a result, the informal street trading sector plays an important role in providing a security net for millions of unemployed in the South African economy. However, informal street trading is not without its problems (Willemse, 2011:7). Often people blame government for not creating employment. When government is unable to provide sustainable employment to all the people, informal jobs emerge. Thus informal trading has become the only option for survival. Informal trading is a major source of income for the majority of the urban poor and therefore requires a properly regulated environment to address issues of income and unemployment for the poor. This study undertook to investigate how Polokwane Local Municipality regulates informal trading in the city of Polokwane. The research method employed in this study is qualitative. The main finding of the study is that because informal trading plays a significant role in creating employment, it must be well regulated and supported by the municipality in order to be organised. The main recommendation on the basis of this finding is that there should be a new approach, especially in terms of enforcement of by-laws. Most informal traders have applied for permits and have been waiting for a response from the Polokwane Local Municipality for years. In this regard, most of the informal traders are dissatisfied with municipal treatment of informal trading in the city. This dissatisfaction is also caused by lack of consultation.
Keywords: Informal trading; Informal traders; Polokwane Local Municipality; By-laws; Trade regulations; Street vendors -- South Africa -- Limpopo; Peddlers and peddling -- South Africa -- Limpopo; Informal sector (Economics) -- South Africa -- Limpopo